Biomanipulation: Universal Soft Robotic Microgripper (Small 4/2019). Issue 4 (24th January 2019) - Jia, Haiyan; Mailand, Erik; Zhou, Jiangtao; Huang, Zhangjun; Dietler, Giovanni; Kolinski, John M.; Wang, Xinling; Sakar, Mahmut Selman
Abstract : Gripping and holding of microscale objects are key tasks for robotic biomanipulation. However, the size and mechanical properties of biological samples show high variability, and they are sensitive to external forces. In article number1803870, Xinling Wang, Mahmut Selman Sakar, and co‐workers present a simple yet highly adaptive engineering solution for the gentle manipulation of a wide range of microscale objects with arbitrary morphology. Wireless control of actuation enables minimally invasive operations.